Impact of the Distance Travelled to School on Students' Performance, Tardiness, and Absenteeism in Public Schools in Morocco - Hamid Bammou; Mohammed El Bouhali; Aicha El Alaoui (European Scientific Journal, ESJ, 2024)
The challenges of providing equitable access to quality education are particularly acute in rural areas, where the distance pupils have to travel to school can have a significant impact on their academic performance. This study addresses the critical question: How does the distance students have to travel to school affect their academic outcomes? Focusing on a primary school in a rural area of Morocco, the research aims to analyze the relationship between students' travel times and their academic performance. Based on a statistical analysis of data collected from 220 students, the study uses univariate analysis, ANOVA, and Pearson correlation tests to examine the effects of commute time on tardiness, absenteeism, and academic performance. The results indicate that longer commute times are associated with higher rates of tardiness and absenteeism, as well as lower student performance. These findings highlight the urgent need to address logistical challenges in rural areas in order to improve educational outcomes. The study concludes by emphasizing the need for targeted interventions, such as improved transport infrastructure, to mitigate the negative impact of long commutes on student performance.